Theatre After Empire (Taylor & Francis, 2024)
Emphasizing the resilience of theatre arts in the midst of significant political change, Theatre After Empire spotlights the emergence of new performance styles in the wake of collapsed political systems. Centering on theatrical works from the late nineteenth century to the present, twelve original essays written by prominent theatre scholars showcase the development of new work after social revolutions, independence campaigns, the overthrow of monarchies, and world wars. Global in scope, this book features performances occurring across Africa, the Americas, Asia, Europe, and the Middle East. The essays attend to a range of live events-theatre, dance, and performance art-that stage subaltern experiences and reveal societies in the midst of cultural, political, and geographic transition. This collection is an engaging resource for students and scholars of theatre and performance; world history; and those interested in postcolonialism, multiculturalism, and transnationalism.
English
Keywords: General and world history; Theatre studies; postcolonial,decolonization,colonial,nationalism,Hapsburg,Ottoman,Czechoslovakia,Oh Taesuk,Rotimi,tanguedia,apartheid,Meena Kumari,John Ruganda,National Theatre Movement,Hanay Geiogamah,Colonial Administration,Francis Imbuga,La Cage Aux Folles,Quare Fellow,George III,Asian American Actors,Grotesco Criollo,Spoken Drama,Van Graan,Sultan Selim III,Turkish Theatre,African Personality,Diva Worship,Chickencoop Chinaman,Baby Stroller,Kim Family,Concert Party,OSF,Geek Theatre,Asian American Theatre,Komedie Stamboel